Does the reliability of institutions affect public good contributions? Evidence from a laboratory experiment - Björn Jahnke; Martin Fochmann; Andreas Wagener (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Reliable institutions - i.e., institutions that live up to the norms that agents expect them to keep - foment cooperative behavior. We experimentally confirm this hypothesis in a public goods game with a salient norm that cooperation was socially demanded and corruption ought not to occur. When nevertheless corruption attempts came up, groups that were told that "the system" had fended off the attempts made considerably higher contributions to the public good than groups that only learned that the attempt did not aect their payoffs or that were not at all exposed to corruption.
Keywords: H41; A13; C91; 330